2014
DOI: 10.1002/2013wr015200
|View full text |Cite
|
Sign up to set email alerts
|

Improving nutrient management practices in agriculture: The role of risk‐based beliefs in understanding farmers' attitudes toward taking additional action

Abstract: A recent increase in the amount of dissolved reactive phosphorus (DRP) entering the western Lake Erie basin is likely due to increased spring storm events in combination with issues related to fertilizer application and timing. These factors in combination with warmer lake temperatures have amplified the spread of toxic algal blooms. We assessed the attitudes of farmers in northwest Ohio toward taking at least one additional action to reduce nutrient loss on their farm. Specifically, we (1) identified to what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…However, the sign and effect of each of these characteristics are not always consistent, which may have to do with variation in the types of practices analyzed and the confluence of other factors discussed above. Additionally, habits, or behaviors practiced regularly, improves the fit of behavioral change models (Klöckner 2013) and past/current practices can be an important variable for understanding adoption of agricultural conservation practices in particular (Wilson et al 2014). Smit et al (2000) included the evaluation concept in their typology of adaptation in order to highlight the importance of measuring outcomes associated with adaptive actions, which can enable an assessment of whether adaptive actions reduce or increase vulnerability.…”
Section: Conceptual Framework For Agricultural Adaptationmentioning
confidence: 99%
“…However, the sign and effect of each of these characteristics are not always consistent, which may have to do with variation in the types of practices analyzed and the confluence of other factors discussed above. Additionally, habits, or behaviors practiced regularly, improves the fit of behavioral change models (Klöckner 2013) and past/current practices can be an important variable for understanding adoption of agricultural conservation practices in particular (Wilson et al 2014). Smit et al (2000) included the evaluation concept in their typology of adaptation in order to highlight the importance of measuring outcomes associated with adaptive actions, which can enable an assessment of whether adaptive actions reduce or increase vulnerability.…”
Section: Conceptual Framework For Agricultural Adaptationmentioning
confidence: 99%
“…It is likely that this farmer is the one who will further adjust their practices in response to thoughtful recommendations made by trusted advisors. Thus, we present a clarion call to consider not only agronomic provisioning and economics in fertility recommendation, but also the potential for environmental degradation, and to provide more holistic and tailored recommendations to the farming population who is largely ready and willing to adjust their practices (Wilson et al 2014).…”
Section: Moving Forwardmentioning
confidence: 99%
“…Valentin et al (2004) surveyed farmers in Kansas and found in-field practices that saved nutrients increased farm profitability, while practices designed to save soil did not influence profitability. Wilson et al (2014) found that a perception of risk to either profitability or water quality was the best predictor of farmer attitudes towards adopting a new practice in northwest Ohio and emphasized the importance of efficacy, or a belief that specific farm management changes can make a difference. Also in Ohio, Campbell et al (2011) used a mixture of qualitative and quantitative methods to analyze the role of collaboration in driving behavior change and found that those participating in grass-roots partnerships had increased levels of adoption.…”
Section: Best Management Practices At the Watershed Scalementioning
confidence: 99%